2007
DOI: 10.7861/clinmedicine.7-1-28
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of atrial fibrillation

Abstract: -Atrial fibrillation (AF) continues to offer a management challenge to physicians. The incidence of this arrhythmia is rising and the cost to the healthcare system is vast. Much of this health burden relates to the high risk of stroke and thromboembolism associated with AF. This review covers common treatment strategies employed in AF management, discusses relevant drug therapy and the role of electrophysiology or surgery.KEY WORDS: antiarrhythmic drugs, atrial fibrillation, stroke, thromboembolic prophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Among many clinical populations, patients with atrial fibrillation were identified as one of the high‐risk groups for reporting uncertainty that resulted in negative outcomes including anxiety, depression and low perceived health (Kang 2002). Although atrial fibrillation is the most common cardiac rhythm disturbance in clinical practice, the treatments of this disorder are very complicated, and no single accepted approach to the management of atrial fibrillation exists (Watson et al. 2007).…”
Section: Background and Significancementioning
confidence: 99%
“…Among many clinical populations, patients with atrial fibrillation were identified as one of the high‐risk groups for reporting uncertainty that resulted in negative outcomes including anxiety, depression and low perceived health (Kang 2002). Although atrial fibrillation is the most common cardiac rhythm disturbance in clinical practice, the treatments of this disorder are very complicated, and no single accepted approach to the management of atrial fibrillation exists (Watson et al. 2007).…”
Section: Background and Significancementioning
confidence: 99%
“…According to prevalence surveys, approximately 2% of the population has AF, and its incidence increases with age [14]. The mechanism that causes AF is generally believed to be the extremely rapid abnormal discharges in the atrial tissue, resulting in the inability of the atria to contract normally and irregular heartbeat [15]. AF is caused by the atrium replacing the sinus node that normally sends out electrical signals, resulting in a rapid and disorderly heartbeat during the attack [16].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) isas regarded as the most common heart arrhythmia which is seen in clinical pratctice [16,17] . Atrial fibrillation can induce or exacerbate heart failure, myocardial infarction, thromboembolism, cerebral infarction [18] and chronic renal failure [19] , which all negatively affect the quality of life and increase the duration of hospital stay [20,21] . More than 1% of adults develop AF, and the prevalence of AF increases with age [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, over 2 million people in the United States suffer from AF. The cost of continuous examinations and increased rates of hospitalization of AF patients amounted to 459 million Euro in 2000 [20,21,23,24] . Predictions suggest that the world will face a 2.5-fold increase in the prevalence of AF by the year 2050 [25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation